LOCAL AND ETHNOFOLKLORE CHARACTERISTICS OF WEDDING AND CEREMONIAL SONGS IN THE SURXONDARYO OASIS - Manzura Narziqulova (International Journal of Literature and Language Studies, 2026)
Abstract This article explores the unique local and ethnofolklore characteristics of wedding and family-household ceremonial songs in the Surxondaryo oasis of Uzbekistan, utilizing the authentic materials of the regional dissertation. It analyzes the ritualistic, mythological, and poetic dimensions of ceremonies related to childbirth, the cradle period (beshik toyi), circumcision (khatna toyi), and marriage. Unique local phenomena such as the cult of "Tuvgich Momo," the "Qavzoq" masked dance, the "Chanki" women's gathering, and specific wedding customs like "jaloq qizartirar" are thoroughly investigated. Employing an analytical and objective approach, the study evaluates how these traditions reflect the ancient animistic, totemistic, and social worldviews of the oasis population, highlighting their significance as vital monuments of Uzbek cultural heritage while emphasizing the necessity of rigorous scientific verification of oral folklore data.